Motorcycle helmet for children. - Radin Sohadi, Radin Umar; Wong, Shaw Voov; Hamouda, Abdel Magid Salem; Megat Ahmad, Megat Mohamad Hamdan; Ong, Wei Yang (2003)

(untitled)
The protective crash helmet includes an outer shell, an inner shell, comfort padding and a good retention system. The outer shell is constructed of fiber-reinforce composites or thermoplastics and the inner shell is constructed of a preselected light weight material having high flexible element for absorbing and distributing the impact energy received by the outer shell. An impact absorbing layer that forms the inner shell of the protective helmet is embedded equally within the said outer shell. The impact absorbing layer is made of expanded polystyrene styrofoam (EPS) with relatively low density. The impact absorbing layer of the inner shell has a substantially uniform thickness of approximately 20 - 30 mm which provide the optimum compromise between the shock absorbing performance and the aerodynamic and mass limitation of the helmet and the outer shell having the thickness in the range of 1 to 10 mm.